Prospect for Settlement of Sharia Insurance Disputes Through The Indonesian National Sharia Arbitration Board - Hartati, Sawitri Yuli; Windiani, Arovah; Mardani, Mardani (Faculty of Law, Universitas Jenderal Soedirman, 2024)
The contract between sharia insurance companies and policyholders is based on sharia principles, namely helping each other to protect each other. However, if disputes still occur,a resolution can be reached through mediation, sharia arbitration, and the courts. The problem in this research is how practices and obstacles resolve sharia insurance disputes through sharia arbitration institutions and how, ideally, arrangements in sharia insurance cases through sharia arbitration institutions can be resolved. The research methods used an analytical perspective, namely an investigation aiming to provide an overview or formulate a problem according to existing circumstances/facts. So it is necessary to revise the Arbitration and Alternative Dispute Resolution Law (1999), especially Article 61, Article 62, Article 63, Article 64, and Article 65, to regulate the scope, duties, and functions of sharia arbitration by considering the use of virtual arbitration processes in developing sharia arbitration as a special, authoritative, and independent arbitration forum.Keywords: Dispute Resolution; Sharia Arbitration; Sharia Insurance.